Antibacterial Efficacy of Silver Diamine Fluoride Compared to Casein Phosphopeptide-Amorphous Calcium Phosphate Against Streptococcus mutans in a Biofilm Caries Model - Sanaa N. Al-Haj Ali; Shahed Al-Ogayyel; Ra'fat I. Farah (Association of Support to Oral Health Research (APESB), 2023)
Objective: To compare the antibacterial efficacy of silver diamine fluoride (SDF) with a product containing casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) against Streptococcus mutans using a biofilm caries model. Material and Methods: Twenty-seven saliva-coated dentine blocks obtained from extracted human teeth were inoculated with Streptococcus mutans monospecies biofilm in this in vitro study. The biofilms were then exposed to 10% sucrose in brain heart infusion broth eight times daily for seven days. After the biofilm growth period, the dentine blocks (n=9 per group) were treated with one of the following substances: 1) sterile saline (control), 2) 38% SDF, and 3) a product containing CPP-ACP. Then, the samples were incubated at 37ºC for 48 hours, and the numbers of viable microorganisms in the biofilms were counted and compared. ANOVA and Tukey's HSD tests were used to analyze the data (p<0.05). Results: The number of viable bacteria, as determined by the number of colony-forming units (CFU mL-1) of Streptococcus mutans, was significantly reduced following treatment with SDF and the CPP-ACP product (p<0.05). However, SDF showed superior antibacterial activity compared to the CPP-ACP product (mean CFU mL-1=zero compared to 96 x106) (p<0.05). Conclusion: SDF has higher antibacterial activity against cariogenic Streptococcus mutans biofilm than the CPP-ACP product. The CPP-ACP product showed antibacterial activity, but it was limited.